Caspase-2 and JNK activated by saturated fatty acids are not involved in apoptosis induction but modulate ER stress in human pancreatic β-cells - Němcová-Fürstová, Vlasta; Balušíková, Kamila; Srámek, Jan; James, Roger F; Kovář, Jan (Cellular physiology and biochemistry, 2013)
BACKGROUND: Fatty acid-induced apoptosis and ER stress of pancreatic β-cells contribute to the development of type 2 diabetes, however, the molecular mechanisms involved are unclear. AIMS: In this study we have tested the role of caspase-2 and suggested ER stress mediator JNK in saturated fatty acid-induced apoptosis of the human pancreatic β-cells NES2Y. RESULTS: We found that stearic acid at apoptosis-inducing concentration activated ER stress signaling pathways, i.e. IRE1α, PERK and ATF6 pathways, in NES2Y cells. During stearic acid-induced apoptosis, JNK inhibition did not decrease the rate of apoptosis nor the activation of caspase-8, -9, -7 and -2 and PARP cleavage. In addition, inhibition of JNK activity did not affect CHOP expression although it did decrease the induction of BiP expression after stearic acid treatment. Caspase-2 silencing had no effect on PARP as well as caspase-8, -9 and -7 cleavage and the induction of CHOP expression, however, it also decreased the induction of BiP expression. Surprisingly, caspase-2 silencing was accompanied by increased phosphorylation of c-Jun. CONCLUSIONS: We have demonstrated that caspase-2 as well as JNK are not key players in apoptosis induction by saturated fatty acids in human pancreatic β-cells NES2Y. However, they appear to be involved in the modulation of saturated fatty acid-induced ER stress signaling, probably by a mechanism independent of c-Jun phosphorylation.
Keywords: signální transdukce; Phosphorylation; Signal Transduction; DNA-Binding Proteins; Heat-Shock Proteins; Humans; DNA vazebné proteiny; fosforylace; Stearic Acids; Activating Transcription Factor 6; Transcription Factors; Caspase 2; Transcription Factor CHOP; Caspase 7; lidé; kaspasa 2; JNK mitogenem aktivované proteinkinasy; apoptóza; JNK Mitogen-Activated Protein Kinases; RNA, Small Interfering; malá interferující RNA; stres endoplazmatického retikula; kaspasa 7; transkripční faktor ATF6; Caspase 8; Endoplasmic Reticulum Stress; Insulin-Secreting Cells; Poly(ADP-ribose) Polymerases; poly(ADP-ribosa)polymerasy; transkripční faktor CHOP; RNA Interference; kyseliny stearové; kaspasa 8; beta-buňky; transkripční faktory; Caspase 9; kaspasa 9; RNA interference; Apoptosis; proteiny teplotního šoku